Historic Landscapes and Mental Well-being - Barrass, Kerry; Darvill, Timothy (Archaeopress Publishing, 2019)
Using archaeological sites and historic landscapes to promote mental health well-being represents one of the most significant advances in archaeological resource management for many years. Its potential contribution to health-care and wellness initiatives is boundless. Prompted by the Human Henge project working within the Stonehenge and Avebury World Heritage Site, this volume provides an overview of work going on across Britain and the near Continent at many different scales. Contributors share experiences, and discuss the outcomes, implications, and theoretical underpinnings of heritage-based well-being projects.